A correction to "Counting rational points on a certain exponential-algebraic surface''. - Pila, J (Association des Annales de l'Institut Fourier, 2017)
This note is to correct a part of the paper [1]. All the theorems remain correct (though some of the implied constants will be adversely affected). I am very grateful to John Armitage for pointing out my error. The mistake occurs in the early lines of the proof of Theorem 6.1, page 507.